2008
DOI: 10.1038/ejhg.2008.105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity patterns at the human clock gene period 2 are suggestive of population-specific positive selection

Abstract: Period 2 (PER2) is a key component of the mammalian circadian clock machinery. In humans, genetic variation of clock genes or chronic disturbance of circadian rhythmicity has been implied in the onset of several phenotypes, ranging from periodic insomnias to advanced or delayed sleep phases, to more severe disorders. Peculiar geographic diversity patterns in circadian genes might represent an adaptive response to different light/dark cycles or environmental changes to which different human populations are expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
0
37
1
Order By: Relevance
“…In such a case, the methods of analysis may fail to determine positive selection at the macrolevel due to their insufficient power. In addition, selection may work only in some populations, as was reported for the period 2 gene in humans (56). According to the results of the population history analysis, both S1 and S2 species experienced recent population expansion.…”
Section: Discussionmentioning
confidence: 86%
“…In such a case, the methods of analysis may fail to determine positive selection at the macrolevel due to their insufficient power. In addition, selection may work only in some populations, as was reported for the period 2 gene in humans (56). According to the results of the population history analysis, both S1 and S2 species experienced recent population expansion.…”
Section: Discussionmentioning
confidence: 86%
“…Using a similar strategy but investigating several clock and clock-related genes in five ethnic groups, Ciarleglio et al (17) have reported that is unlikely that a pattern of natural selection has shaped the evolutionary process of these genes, suggesting that a random process is involved. On the other hand, Cruciani et al (19) have suggested that polymorphisms in the PER2 gene might have been influenced by natural selection.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies and on the present findings (16,17,19) and considering the history of human migrations around the planet over time, as well as the special characteristics of sunshine and light inherent to each place on earth, it is worth questioning which factors contributed to genetic variations that are specific to each ethnic group, especially considering the clock genes. Since the circadian phenotype is a result of strong interaction between the environment and the organism and the most important Zeitgeber for humans is the light/dark cycle given by the sun (15), it would be logical to think that differences in latitude could contribute in an important manner to the selection of these polymorphisms in different geographical zones.…”
Section: Discussionmentioning
confidence: 99%
“…One study aimed at finding directional selection on circadian clock genes in humans concluded that the genetic variation among world populations was due to genetic drift rather than latitudinal selection [50]. However, another revealed that genetic [51].…”
Section: Latitudinal Variation In Properties Of Circadian Clocksmentioning
confidence: 99%